PENGUJIAN ATAS DEBT/EQUITY HYPOTHESIS DAN SIZE HYPOTHESIS TERHADAP PEMILIHAN METODE PENYUSUTAN ASSET TETAP - Yosefa Sayekti (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2013)
This study aims to examine the debt / equity hypothesis and hypothesis size (political cost hypothesis) with a focus on fixed asset depreciation accounting method selected companies. Debt / equity hypothesis states that if the debt / equity ratio of a company is getting higher, then chances are the company to choose accounting methods that increase profitability also increased (Watts and Zimmerman, 1986). This study uses debt to equity ratio and interest coverage ratio as proxy variables to test the debt / equity hypothesis. While the size hypothesis states that the larger the company, the managers the possibility to choose accounting methods that reduce profits is also higher (Watts and Zimmerman, 1986). This study uses total assets and net income as proxy variables for company size. This study uses a logit regression to test the hypothesis. The total sample of the study was 108 company's financial statements for the year ended December 31, 2004. The results show that the debt / equity hypothesis (the interest coverage ratio as a proxy variable), and the size hypothesis (with total assets as a proxy variable) proved. Overall, the test results are consistent with previous studies. Keywords: debt/equity hypothesis, size hypothesis, logit model